The effect of McCarthy strategy according to learning styles in developing the skills of preparing and receiving volleyball for students - Ahmed Abboodi, Muthanna; Muhammad Farid, Saddam (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research lies in using the McCarthy strategy according to the learning patterns in a scientific manner and commensurate with the capabilities of learners, as researchers believe that it will develop a development in the skills of preparing and receiving volleyball for students.As for the research problem: Through the researchers’ experience and their knowledge of many research studies and their presence in the educational process and their observations of educational units, they noticed that there are a large number of students (learners) in the third stage facing difficulty in mastering the skills of preparation and receiving because they are complex skills and need a great time to master Correctly, researchers believe that the reason is the lack of use of modern teaching methods, so it was necessary this event to receive wide attention through the introduction of new strategies or models in the process of learning and developing the two skills, so researchers felt that going into this experience through the use of McCarthy’s strategy in accordance with For learning styles, the aim of which is to try to master the skills of preparation and receiving quickly, the research aimed to identify the effect of McCarthy strategy according to learning patterns in developing the skills of preparation and receiving of volleyball for students, as well as to identify the preference in the impact between McCarthy strategy according to the learning patterns and the method followed from The teacher agreed to develop the skills of preparing and receiving volleyball.As for the third chapter, the researchers used the experimental approach to solve the research problem, and for the research community, the research community was identified by the third-stage students/College of Physical Education and Sports Science/University of Kufa for the academic year 2018-2019 and they are 60 students and the researchers chose a sample of them by 48. Students were evenly distributed into two groups (experimental and control). Division (b) represented the experimental group, and division (c) the control group, and they are equally classified by (6) students for each of the learning styles of both groups, who were chosen in a simple random manner ( The lottery), as for the most important conclusions were: The use of McCarthy strategy has achieved a remarkable development in the technical performance and accuracy of the skills of preparation and receiving in volleyball for members of the experimental group, the members of the experimental group that used the McCarthy strategy in the technical performance and accuracy of the skills of preparation and receiving in volleyball over Control group members in posttest tests.